2014
DOI: 10.1186/2190-8567-4-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Criticality in Neuronal Avalanches: II. A Theoretical and Empirical Investigation of the Driven Case

Abstract: The observation of apparent power laws in neuronal systems has led to the suggestion that the brain is at, or close to, a critical state and may be a self-organised critical system. Within the framework of self-organised criticality a separation of timescales is thought to be crucial for the observation of power-law dynamics and computational models are often constructed with this property. However, this is not necessarily a characteristic of physiological neural networks—external input does not only occur whe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…For continuous time-series such as the Vm recording, one selects a threshold and a baseline. We defined a neuronal avalanche based on the positive threshold crossing followed by a negative threshold crossing of the Vm time series (Poil et al, 2012;Hartley et al, 2014;Larremore et al, 2014;Karimipanah et al, 2017b). We quantified each neuronal avalanche by (i) its size A, i.e., the area between the curve and the baseline, and (ii) its duration , i.e., the time between threshold crossings ( Figure 2B).…”
Section: Membrane Potential Fluctuations Reveal Signatures Of Criticamentioning
confidence: 99%
“…For continuous time-series such as the Vm recording, one selects a threshold and a baseline. We defined a neuronal avalanche based on the positive threshold crossing followed by a negative threshold crossing of the Vm time series (Poil et al, 2012;Hartley et al, 2014;Larremore et al, 2014;Karimipanah et al, 2017b). We quantified each neuronal avalanche by (i) its size A, i.e., the area between the curve and the baseline, and (ii) its duration , i.e., the time between threshold crossings ( Figure 2B).…”
Section: Membrane Potential Fluctuations Reveal Signatures Of Criticamentioning
confidence: 99%
“…An important property of SOC systems, which is potentially absent in neural activity, is the separation of time scales (STS) (Bak et al, 1987; Drossel and Schwabl, 1992; Clar et al, 1996; Dickman et al, 2000; Pruessner, 2012; Hartley et al, 2013) whereby pauses between avalanches last much longer than the avalanches proper. For example, forest fires last for a much shorter time than it takes to regrow the forest.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, in the classical sandpile model, scale-free avalanche distributions are observed only if the grains are dropped at a low enough rate (Vespignani and Zapperi, 1997, 1998). This low rate of external input, called drive, is a necessary condition for the long pauses and hence for SOC (Bak et al, 1987; Drossel and Schwabl, 1992; Clar et al, 1996; Dickman et al, 2000; Pruessner, 2012; Hartley et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have long sought data to show that the brain operates at a critical state to benefit from the maximal dynamic range of processing, fidelity of information transmission, coherence between multiple "nested" biosemiotic levels [19] and information capacity [74][75][76][77][78][79][80]. A very appropriate marker of criticality may prove to be the percolation transition of interphase water at neurolemmal membranes, e.g.…”
Section: A Novel Hypothesis For Dynamically-structured Water At the Imentioning
confidence: 99%
“…In 2003, Beggs and Plenz [75] showed that in vitro propagation of spontaneous activity in cortical networks obeys a power law, and is described by equations that govern avalanches [62]. They proposed that these so-called "neuronal avalanches" may represent new modes of neuronal network activity [74][75][76], which differ profoundly from oscillatory, synchronized or wave-like network states. They further proposed that in the critical state, the branching network may satisfy competing demands of information transmission and network stability [75].…”
Section: The Self-ordered Criticality Of Biological Watermentioning
confidence: 99%